(untitled) (Fiep Bulletin - online, 2012)
It can easily be observed that the aged do not belong in the standards established by current society. In the social context, they are neither engaged in production nor are they great consumers.Consequently, the aged often feel they do not have much value, except for the knowledge some of them have. In this context there is always some discontent due to the fact that only knowledge can be highlighted in many registers about the aged people. Confronted by such situation, it seems important to question whether other values could be evidenced among senior citizens.